Effect of Ammodaucus leucotrichus Coss. & Dur. Essential Oil on the Viability of Erythrocytes and its Antiradical Activity Assessment - Imad Abdelhamid EL HACI; Wissame MAZARI; Fawzia ATIK-BEKKARA (Journal of Natural Product Research and Applications, 2021)
Plants for medicinal purposes are considered as the main source of health care for the majority of the world population. In order to promote medicinal plants in Algeria, the present work aimed to assess the physico-chemical characterization, hemolytic, and antioxidant activities of Ammodaucus leucotrichus essential oil of an endemic plant from south-west of Algeria. The plant was harvested from the region of Bechar (south-west of Algeria). The oil was obtained by hydrodistillation method using Clevenger apparatus. The antioxidant activity of the oil was carried out using DPPH scavenging assay, and its effect on erythrocyte cells was evaluated by measuring the hemolytic degree. The obtained results showed that this oil presented a low antioxidant activity compared to positive control (ascorbic acid). The hemolytic activity was very low since the oil diluted to 1/10, while it was low in the pure state. This fact proves the safety of A. leucotrichus oil, which can explain its use without risk by the indigenous population. REFERENCES: Abu Zarga, M.H., Al-Jaber, H.I., Baba Amer, Z.Y., Sakhrib, L., Al-Qudah, M.A., Alhumaidi, J.Y.G., Abaza, I.F., & Afifi, FU. (2013). Chemical composition, antimicrobialand antitumor activities of essential oil of Ammodaucus leucotrichus growing in Algeria.Journal of Biologically Active Products from Nature, 3, 224–231.http://doi.org/10.1080/22311866.2013.833469.Adorjan, B., & Buchbauer, G. (2010). Biological properties of essential oils: An updatedreview. Flavour and Fragrance Journal, 25, 407–426. http://doi.org/10.1002/ffj.2024.AFNOR. (1992). Association Française de Normalisation «Recueil des normes françaises surles huiles essentielles». II édition, Paris.Amorati, R., Foti, M.C., & Valgimigli, L. (2013). Antioxidant activity of essential oils.Journal of Agricultural and Food Chemistry, 61, 10835–10847.http://doi.org/10.1021/jf403496k.Bakkali, F., Averbeck, S., Averbeck, D., Idaomar, M. (2008). Biological effects of essentialoils- a review. Food and Chemical Toxicology, 46, 446–475.http://doi.org/10.1016/j.fct.2007.09106.Barao Paixao, V.L., & de Carvalho, J.F. (2021). Essential oil therapy in rheumatic diseases:A systematic review. Complementary Therapies in Clinical Practice, 43, 101391.http://doi.org/10.1016/j.ctcp.2021.101391Benhouhou, S. (2005). A Guide to Medicinal plants in North Africa: database on Medicinalplants, IUCN center for Mediterranean cooperation. Mâlaga.Bouaziz, M., Yangui, T., Sayadi, S., & Dhouib, A. (2009). Disinfectant properties of essentialoils from Salvia officinalis L. cultivated in Tunisia. Food and Chemical Toxicology, 47,2755–2760. http://doi.org/10.1016/j.fct.2009.08.005.Burt, S. (2004). Essential oils: their antibacterial properties applications in foods-a review.International Journal of Food Microbiology, 94, 223–253.http://doi.org/10.1016/j.ijfoodmicro.2004.03.022.Conforti, F., Sosa, S., Marrelli, M., Menichini, F., Statti, G.A., Uzunov, D., Tubaro, A., &Menichini, F. (2009). The protective ability of Mediterranean dietary plants against theoxidative damage: The role of radical oxygen species in inflammation and thepolyphenol, flavonoid and sterol contents. Food Chemistry, 112, 587–594.http://doi.org/10.1016/j.foodchem.2008.06.013.Dalar, A., Türker, M., & Konczak, I. (2012). Antioxidant capacity and phenolic constituentsof Malva neglecta Wallr. and Plantago lanceolata L. from Eastern Anatolia region ofTurkey. Journal of Herbal Medicine, 2, 42–51.http://doi.org/10.1016/j.hermed.2012.03.001.Dawidowicz, A.L., Szewczyk, J., & Dybowski, M.P. (2016). Modified application of HSSPME for quality evaluation of essential oil plant materials. Talanta, 146, 195–202.http://doi.org/10.1016/j.talanta.2015.08.043.El Haci, I.A., Bekhechi. C., Atik-Bekkara, F., Mazari, W., Gherib, M., Bighelli, A.,Casanova, J., & Fellix, T. (2014). Antimicrobial activity of Ammodaucus leucotrichusfruit oil from Algerian Sahara. Natural Product Communications, 9, 711–712.http://doi.org/10.1177/1934578X1400900533 Essid, R., Rahali, F.Z., Msaada, K., Sghair, I., Hammami, M., Bouratbine, A., Aoun, K., &Limam, F. (2015). Antileishmanial and cytotoxic potential of essential oils frommedicinal plants in Northern Tunisia. Industrial Crops and Products, 77, 795–802.http://doi.org/10.1016/j.indcrop.2015.09.049.Fillatre, Y., Rondeau, D., Daguin, A., & Communal, P.Y. (2016). A work flow for multiclassdetermination of 256 pesticides in essential oils by liquid chromatography tandem massspectrometry using evaporation and dilution approaches: Application to lavandin, lemonand cypress essential oils. Talanta, 149, 178–186.http://doi.org/10.1016/j.talanta.2015.11.052.Gainza, Y.A., Domingues, L.F., Perez, O.P., Rabelo, M.D., Lopez, E.R., & Chagas, A.C.S.(2015). Anthelmintic activity in vitro of Citrus sinensis and Melaleuca quinquenerviaessential oil from Cuba on Haemonchus contortus. Industrial Crops and Products, 76,647–652. http://doi.org/10.1016/j.indcrop.2015.07.056.Gomes, M.R.F., Schuh, R.S., Jacques, A.L.B., Dorneles, G.G., Montanha, J., Roehe, P.M.,Bordignon, S., Dallegrave, E., Leal, M.B., & Limberger, R.P. (2013). Biologicalassessment (antiviral and antioxidant) and acute toxicity of essential oils from Drimysangustifolia and D. brasiliensis. Revista Brasileira de Farmacognosia, 23, 284–290.http://doi.org/10.1590/S0102-695X2012005000142.Halla, N., Helenoa, S.A., Costa, P., Fernandes, I.P., Calhelha, R.C., Boucherit, K., Rodrigues,A.E., Ferreira, I.C.F.R., & Barreiro, M.F. (2018). Chemical profile and bioactiveproperties of the essential oil isolated from Ammodaucus leucotrichus fruits growing inSahara and its evaluation as a cosmeceutical ingredient. Industrial Crops and Products,119, 249–254. http://doi.org/10.1016/j.indcrop.2018.04.043.Hammiche, V., & Maiza, K. (2006). Traditional medicine in central Sahara: pharmacopoeiaof Tassili N’ajjer. Journal of Ethnopharmacology, 105, 358–367.http://doi.org/10.1016/j.jep.2005.11.028.Hossain, M.H., Shah, M.D., Sang, S.V., & Sakari, M. (2012). Chemical composition andantibacterial properties of the essential oils and crude extracts of Merremia borneensis.Journal of King Saud University –Science, 24, 243–249.http://doi.org/10.1016/j.jksus.2011.03.006.Hussein, G., Miyashiro, H., Nakamura, N., Hattori, M., Kakiuchi, N., & Shimotohno, K.(2000). Inhibitory effects of Sudanese medical plant extracts on hepatitis C virus (HCV)protease. Phytotherapy Research, 14, 510–516. http://doi.org/10.1002/1099-1573(200011)14:73.0.co;2-b.Idm’hand, E., Msanda, F., & Cherifi, K. (2020). Medicinal uses, phytochemistry andpharmacology of Ammodaucus leucotrichus. Clinical Phytoscience, 6,6.http://doi.org/10.1186/s40816-020-0154-7.Khaldi, A., Meddah, B., Moussaoui, A., & Sonnet, P. (2017). Anti-mycotoxin effect andantifungal properties of essential oil from Ammodaucus leucotrichus Coss. & Dur. onAspergillus flavus and Aspergillus ochraceus. Journal of Essential Oil and BearingPlants, 20, 36–44. http://doi.org/10.1080/0972060X.2017.1282840.Lee, J.Y., Cho, P.Y., Kim, T.Y., Kang, S.Y., Song, K.Y., & Hong, S.J. (2002). Hemolyticactivity and developmental expression of pore-forming peptide, clonorin. Biochemicaland Biophysical Research Communications, 296, 1238–1244.http://doi.org/10.1016/s0006-291x(02)02062-4.Manssouri, M., Znini, M., & Majidi, L. (2020). Studies on the antioxidant activity of essentialoil and various extracts of Ammodaucus leucotrichus Coss. & Dur. fruits from Morocco.Journal of Taibah University for Science, 14, 124–130.http://doi.org/10.1080/16583655.2019.1710394. Pavlović, I., Petrović, S., Radenković, M., Milenković, M., Couladis, M., Branković, S.,Pavlović, M.D., & Niketic, D.M. (2012). Composition, antimicrobial, antiradical andspasmolytic activity of Ferula heuffelii Griseb. ex Heuffel (Apiaceae) essential oil. FoodChemistry, 130, 310–315. http://doi.org/10.1016/j.foodchem.2011.07.043.Pillai, S., Mahmud, R., Lee, W.C., & Perumal, S. (2012). Anti-parasitic Activity of Myristicafragrans Houtt. essential oil against Toxoplasma Gondii parasite. APCBEE Procedia, 2,92–96. http://doi.org/10.1016/j.apcbee.2012.06.017.Quezel, P., & Santa, S. (1963). Nouvelle flore de l’Algérie et des régions désertiquesméridionales, CNRS, Paris.Riaz, M., Rasool, N., Bukhari, I.H., Shahid, M., Zubair, M., Rizwan, K., & Rashid, U.(2012). In vitro antimicrobial, antioxidant, cytotoxicity and GC/MS analysis of Mazusgoodenifolius. Molecules, 17, 14275–14287. http://doi.org/10.3390/molecules171214275Sadaoui, N., Bec, N., Barragnan-Montero, V., Kadri, N., Cuisinier, F., Larroque, C., Arab,K., & Khettal, B. (2018). The essential oil of Algerian Ammodaucus leucotrichus Coss.& Dur. and its effect on the cholinesterase and monoamine oxidase activities.Fitoterapia, 130, 1–5. http://doi.org/10.1016/j.fitote.2018.07.015Saleh, M.A., Clark, S., Woodard, B., & Deolu-Sobogun, S.A. (2010). Antioxidant and freeradical scavenging activities of essential oils. Ethnicity and Disease, 20 Suppl 1, 78–82.Salem, M.Z.M., Zidan, Y.E., Mansour, M.A.M., El Hadidi, N.M.N., & Abo Elgat, W.A.A.(2016). Antifungal activities of two essential oils used in the treatment of threecommercial woods deteriorated by five common mold fungi. InternationalBiodeterioration and Biodegradation, 106, 88–96.http://doi.org/10.1016/j.ibiod.2015.10.010.Sebaaly, C., Charcosset, C., Stainmesse, S., Fessi, H., & Greige-Gergesa, H. (2016). Cloveessential oil-in-cyclodextrin-in-liposomes in the aqueous and lyophilized states: fromlaboratory to large scale using a membrane contactor. Carbohydrate Polymers, 138, 75–85. http://doi.org/10.1016/j.carbpol.2015.11.053.Sharma, P., Sharma, J.D. (2001). In vitro hemolysis of human erythrocytes by plant extractswith antiplasmodial activity. Journal of Ethnopharmacology, 74, 239–243.http://doi.org/10.1016/S0378-8741(00)00370-6.Tampieri, M.P., Galuppi, R., Macchioni, F., Carelle, M.S., Falcioni, L., Cioni, P.L., &Morelli, I. (2005). The inhibition of Candida albicans by selected essential oils and theirmajor components. Mycopathologia, 159, 339–345. http://doi.org/10.1007/s11046-003-4790-5.Turek, C., & Stintzing, F.C. (2012). Impact of different storage conditions on the quality ofselected essential oils. Food Research International, 46, 341–353.http://doi.org/10.1016/j.foodres.2011.12.028.Velasco-Negueruela, A., Pérez-Alonso, M.J., Pérez de Paz, P.L., Palá-Paúl, J., & Sanz, J.(2006). Analysis by gas chromatography-mass spectrometry of the volatiles from thefruits of Ammodaucus leucotrichus subsp. leucotrichus and subsp. nanocarpus grown inNorth Africa and the Canary Islands, respectively. Journal of Chromatography A, 1108,273–275. http://doi.org/10.1016/j.chroma.2006.01.031.